Adsorption-desorption of hydrocarbons on complex alkoxides of group I and III metals; Petroleum chemistry; Vol. 37, iss. 1 - Dmitriyeva Z. T.; Tikhonova L. D.; Mezhibor N. G.; Erofeev V. I. Vladimir Ivanovich (1997, 1997)
A study has been made of the kinetics of adsorption-desorption of hydrocarbons by complexes and solvatocomplexes [tert-C₄ H₉ OB(OR)₃ ]Li, [tert-C₄ H₉ OAl(OR)₃ ]Li, [tert-C₄ H₉ OB(OR)₃ ]Li nROH (R = C₄ H₉ , C₇ H₁₅ , C₁₀ H₂₁ ; n = 0, 1.8) as a function of their structure. The kinetic and thermodynamic parameters of thermal desorption of hydrocarbons from complexes have been determined.